Effectiveness Of The Concept Of The Concept Of The Material Of The Rutinity Of Islam's Religious Ways In The Grade Vi Students With Handling The Simulation Of Right Pesantren Activities In Sd Negeri 29 Koto Panjang 2015/2016 - Erman Erman (Fakultas Sastra Universitas Ekasakti, 2017)
This research was conducted to grade 6 students of SD Negeri 29 Koto Panjang Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan Lesson Year 2015/2016. The method used in this research is classroom action research method, data collection through observation, interview and test or assignment, while data analysis is done with interactive model. While the activity is done in an interactive form with the process of collecting data as a cycle process. The results showed that through the method of simulation can improve the activity and learning outcomes of Islamic religious education students Class VI SD Negeri 29 Koto Panjang year 2015/2016 lessons. Student learning activity from initial condition of second cycle there is improvement for improvement.